2022
DOI: 10.3390/ijms23168856
|View full text |Cite
|
Sign up to set email alerts
|

TMAO Suppresses Megalin Expression and Albumin Uptake in Human Proximal Tubular Cells Via PI3K and ERK Signaling

Abstract: Trimethylamine-N-oxide (TMAO) is a uremic toxin, which has been associated with chronic kidney disease (CKD). Renal tubular epithelial cells play a central role in the pathophysiology of CKD. Megalin is an albumin-binding surface receptor on tubular epithelial cells, which is indispensable for urine protein reabsorption. To date, no studies have investigated the effect of TMAO on megalin expression and the functional properties of human tubular epithelial cells. The aim of this study was first to identify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…We have previously shown that TMAO induced increased renal fibroblast proliferation and collagen production via Akt and mTOR, but not via PI3K 22 . We have also shown that TMAO can reduce megalin expression in proximal tubular cells via PI3K and ERK 28 . In addition, TMAO has been linked to promote vascular inflammation via ERK activation 29 .…”
Section: Discussionmentioning
confidence: 55%
“…We have previously shown that TMAO induced increased renal fibroblast proliferation and collagen production via Akt and mTOR, but not via PI3K 22 . We have also shown that TMAO can reduce megalin expression in proximal tubular cells via PI3K and ERK 28 . In addition, TMAO has been linked to promote vascular inflammation via ERK activation 29 .…”
Section: Discussionmentioning
confidence: 55%
“…The suppression is mediated by an effect on PI3K (phosphoinositide 3-kinase) and ERK signaling and could be countered by candesartan, enalapril, and dapagliflozin. 125 A mediation analysis of the European MetaCardis study demonstrated a causal relation between TMAO and declined kidney function, which was corroborated by in vitro studies in human kidney fibroblasts showing that TMAO aggravated kidney fibrosis by ERK1/2 hyperactivation synergistically with TGF-β1 signaling. 126 A TMAO- or choline-supplemented diet in mice caused increased tubulointerstitial fibrosis and deposition of collagen, which was associated with an increased phosphorylation of Smad3.…”
Section: Kidney Toxicity Of Uremic Toxinsmentioning
confidence: 85%
“…We then showed that both CFT073 and TMAO could respectively increase the phosphorylation of ERK 1/2 in bladder epithelial cells. We and others have shown that ERK 1/2 is important for UPECmediated cytokine/chemokine release [15,21,22] and TMAO-mediated inflammation [23,24]. Furthermore, we also evaluated if TMAO by itself could increase the bacterial growth of CFT073 and through that be responsible for the increased release of inflammatory mediator.…”
Section: Discussionmentioning
confidence: 95%
“…We chose to use IL-8 as our inflammatory marker, as it is one of the most important chemokines during a UTI [19,20]. We investigated the involvement of ERK1/2, as it has been shown to be important for UPEC-mediated cytokine/chemokine release [15,21,22] and TMAO-mediated inflammation [23,24]. We found, by using a ERK 1/2 inhibitor, that the IL-8 release induced by CFT073 alone or in combination with TMAO was dependent on ERK 1/2 signaling (Figure 5A).…”
Section: Cft073 and Tmao Mediate The Release Of Il-8 From Bladder Epi...mentioning
confidence: 99%